Transformational Leadership Based Approach to Islamic Education Management: Improving the Quality of Learning and Developing Student Character - Supriatna, Dasep (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Islamic education institutions face the dual challenge of maintaining high academic standards while nurturing moral character in alignment with Islamic principles. This study aims to identify effective management strategies that enhance both learning quality and student character development. A mixed-methods design was employed, integrating qualitative case studies and quantitative surveys from selected Islamic educational institutions. The study is guided by Transformational Leadership Theory and Social Cognitive Theory (Bandura, 2024). Transformational leadership practices positively influenced school climate, teacher motivation, and students’ academic and moral self-efficacy. Effective management fostered collaboration and modeled ethical behavior, contributing to holistic student development. Strategic educational management grounded in leadership and cognitive-social theories is essential for achieving academic excellence and character formation in Islamic schools.